2012
DOI: 10.1364/oe.20.029751
|View full text |Cite
|
Sign up to set email alerts
|

Sol-gel derived ionic copper-doped microstructured optical fiber: a potential selective ultraviolet radiation dosimeter

Abstract: We report the fabrication and characterization of a photonic crystal fiber (PCF) having a sol-gel core doped with ionic copper. Optical measurements demonstrate that the ionic copper is preserved in the silica glass all along the preparation steps up to fiber drawing. The photoluminescence results clearly show that such an ionic copper-doped fiber constitutes a potential candidate for UV-C (200-280 nm) radiation dosimetry. Indeed, the Cu⁺-related visible photoluminescence of the fiber shows a linear response t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(28 citation statements)
references
References 28 publications
0
28
0
Order By: Relevance
“…In fact, radiation‐induced luminescence phenomena related to the Cu + in Cu‐doped glasses have been widely investigated. However, many of these studies have focused on the thermoluminescence, optically stimulated luminescence, lyo—and mechano‐luminescence phenomena, or scintillation properties . Investigations of the RPL phenomena of Cu are very limited .…”
Section: Introductionmentioning
confidence: 99%
“…In fact, radiation‐induced luminescence phenomena related to the Cu + in Cu‐doped glasses have been widely investigated. However, many of these studies have focused on the thermoluminescence, optically stimulated luminescence, lyo—and mechano‐luminescence phenomena, or scintillation properties . Investigations of the RPL phenomena of Cu are very limited .…”
Section: Introductionmentioning
confidence: 99%
“…Cu incorporated in the core of germano-silicate optical fiber is known to exist as Cu 2+ and Cu + ions in the glass network during the high temperature fiber fabrication process [12,13]. And we have found that the Cu ions are involved in the formation of radiation-induced defect centers in the optical fiber that affect the magneto-optical properties.…”
Section: Introductionmentioning
confidence: 94%
“…The distinct peak near 5 eV can be assigned as a transition from the Cu + acceptor state to the conduction band in Figs. 3(b) [5].…”
Section: Photoluminescence Excitation Spectramentioning
confidence: 99%
“…The Cu ion has been widely used for its capability to induce a novel visible emission for the group II-VI semiconductors, ZnO, photonic crystal fiber, and so on, in addition to ferromagnetism [3][4][5]. In this research, we newly synthesized Cu-ion-doped SrHfO 3 (SHO:Cu) compounds and investigated their electronic properties.…”
Section: Introductionmentioning
confidence: 99%